Cambodia Environment Monitor 2008 : Special Focus - Conservation Area Management (World Bank, Washington, DC, 2017)
The Cambodia environment monitor 2008 is one of a series of environmental reports prepared for East Asian countries under an initiative sponsored by the World Bank. The objective of this series is to present a snapshot of environmental trends across a range of issues. The purpose of the monitor is to engage and inform interested stakeholders about key environmental changes in an easy to understand format accessible to a wide audience. This report identifies seven strategic priorities for the Royal government of Cambodia and its conservation partners. 1)articulate a clear and shared vision and re-commitment to conservation goals and objectives; 2)formalize a meaningful enabling legal and regulatory framework for management and protection of conservation areas; 3)formulate clear strategies for recognizing and improving community benefit sharing in conservation areas; 4) strengthen mechanisms for institutional coordination across the ministries; 5) adopt new approaches and paradigms for conservation areas management; 6) with donors, develop and secure sustainable sources of funding for conservation; and 7) reinforce the human resource capacity to implement and manage conservation areas.